The Centennial of a Romanian Mathematical School – A Tribute to its Founder Professor Alexandru Myller - Constantin Corduneanu (Memoirs of the Scientific Sections of the Romanian Academy)
This article is a brief account of the life and struggle of Alexandru Myller for creating a research mathematical department at the University of Iaşi, Romania.